(untitled) (Oxford, 1996)
The book presents both change and continuity, revolutions, and stability - in economics, culture, and warfare, as well as in politics and society - while the great wealth of illustrations complements the text at every stage
Keywords: Châu Âu,Châu Âu; Lịch sử,Lịch sử; 1789-1900,Thế kỷ XX